Podane wyrażenia można zapisać w prostszej postaci. Wyglądają one wówczas następująco:
- 2√7 + 6 (podpunkt a),
- 9 - 6√5 (podpunkt b),
- 3√6 - 3 (podpunkt c),
- 22√3 (podpunkt d),
- 8∛2 (podpunkt e),
- -19 - 4∛7 (podpunkt f).
Skąd to wiadomo?
Zadanie a
6√7 + 2· (3 - 2√7) = 6√7 + 6 - 4√7 = 2√7 + 6
Zadanie b
3 - 2√5 - (4√5 - 6) = 3 - 2√5 - 4√5 + 6 = 9 - 6√5
Zadanie c
-3√6 - 3 · (1 - 2√6) = -3√6 - 3 + 6√6 = 3√6 - 3
Zadanie d
5 · (2 + 4√3) + 2 · (√3 - 5) = 10 + 20√3 + 2√3 - 10 = 22√3
Zadanie e
3 · (2 - ∛2) - (5∛2 + 4) = 6 - 3∛2 - 5∛2 - 4 = 2 - 8∛2
Zadanie f
-2 · (5 - ∛7) - 3 · (2∛7 + 3) = -10 + 2∛7 - 6∛7 - 9 = -19 - 4∛7
#SPJ2